TiO2/Halloysite Composites Codoped with Carbon and Nitrogen from Melamine and Their Enhanced Solar-Light-Driven Photocatalytic Performance. (16th November 2015) - Yao, Pengcheng; Zhong, Shuhui; Shen, Zhurui
Abstract : Carbon (C) and nitrogen (N) codoped anatase TiO2 /amorphous halloysite nanotubes (C+N-TiO2 /HNTs) were fabricated using melamine as C and N source. The samples prepared by different weight ratios of melamine and TiO2 were investigated by X-ray diffraction (XRD) and UV-vis diffuse reflectance spectrometer. It is shown that the doping amounts of C and N could influence the photocatalytic performance of as-prepared composites. When the weight ratio of melamine/TiO2 is 4.5, the C+N-TiO2 /HNTs exhibited the best photocatalytic degradation efficiency of methyl blue (MB) under solar light irradiation. The obtained C+N-TiO2 /HNTs were characterized by transmission electron microscopy (TEM), N2 adsorption-desorption isotherm (BET), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectrum (FT-IR). The results showed that the aggregation was effectively reduced, and TiO2 nanoparticles could be uniformly deposited on the surface of HNTs. This leads to an increase of their specific surface area. XPS and FT-IR analyses indicated TiO2 particles were doped successfully with C and N via the linkage of the Ti–O–N, O–Ti–N, and Ti–O–C. Photocatalytic experiments showed that C+N-TiO2 /HNTs had higher degradation efficiency of MB than TiO2 /HNTs. This makes the composite a potential candidate for the photocatalytic wastewater treatment.